How Does Autologous Breast Reconstruction Impact Downtime? - Zoccali, Giovanni; Rais, Daniel Simon; Farhadi, Jian (Journal of Reconstructive Microsurgery, 2018)
Background Although autologous breast reconstruction is technically quite demanding, it offers the best outcomes in terms of durable results, patient perceptions, and postoperative pain. Many studies have focused on clinical outcomes and technical aspects of such procedures, but few have addressed the impact of various flaps on patient recovery times. This particular investigation entailed an assessment of commonly used flaps, examining the periods of time required to resume daily activities.Methods Multiple choice questionnaires were administered to 121 patients after recovery from autologous reconstruction to determine the times required in returning to specific physical activities. To analyze results, the analysis of variance F-test was applied, and odds ratios (ORs) were determined.Results Among the activities surveyed, recovery time was not always a function of free-flap surgery. Additional treatments and psychological effects also contributed. Adjuvant chemotherapy increased average downtime by 2 weeks, and postoperative irradiation prolonged recovery as much as 4 weeks. Patient downtime was unrelated to flap type, ranging from 2.9 to 21.3 weeks for various activities in question. Deep inferior epigastric perforator (DIEP) flaps yielded the highest OR and transverse upper gracilis (TUG) flaps the lowest.Conclusion Compared with superior gluteal artery perforator and TUG flaps, the DIEP flap was confirmed as the gold standard in autologous breast reconstruction, conferring the shortest recovery times. All adjuvant therapies served to prolong patient recovery as well. Surgical issues, patient lifestyles, and donor-site availability are other important aspects of flap selection.
Keywords: autologous breast reconstruction; breast cancer treatment; downtime; recovery time